2017
DOI: 10.1007/s11121-017-0855-4
|View full text |Cite
|
Sign up to set email alerts
|

The Cascading Effects of Multiple Dimensions of Implementation on Program Outcomes: a Test of a Theoretical Model

Abstract: This study tests a theoretical cascade model in which multiple dimensions of facilitator delivery predict indicators of participant responsiveness, which in turn lead to improvements in targeted program outcomes. An effectiveness trial of the 10-session New Beginnings Program for divorcing families was implemented in partnership with four county-level family courts. This study included 366 families assigned to the intervention condition who attended at least one session. Independent observers provided ratings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
(58 reference statements)
4
27
0
Order By: Relevance
“…This is another reason why some courses have higher subscriptions over other similar courses. Earlier researchers have also found a relationship between facilitator quality and the listener's performance (Paulus, Larey, & Ortega, 1995;Higginbotham & Myler, 2010;Berkel et al, 2018). Thus in line with earlier research works, we also suppose: H4: Facilitator quality (quality values) has a positive influence on intention to use the e-Learning platform.…”
Section: Quality Valuessupporting
confidence: 86%
See 1 more Smart Citation
“…This is another reason why some courses have higher subscriptions over other similar courses. Earlier researchers have also found a relationship between facilitator quality and the listener's performance (Paulus, Larey, & Ortega, 1995;Higginbotham & Myler, 2010;Berkel et al, 2018). Thus in line with earlier research works, we also suppose: H4: Facilitator quality (quality values) has a positive influence on intention to use the e-Learning platform.…”
Section: Quality Valuessupporting
confidence: 86%
“…Unlike what earlier researchers (Ali et al, 2018;Albelbisi & Yusop, 2019) have found, the study results show that course quality has no significant relationship with intention to take up courses from an e-Learning platform. However, what earlier researchers have found (Higginbotham & Myler, 2010;Berkel et al, 2018;Belanger & Carter, 2008;Seufert, 2012;Silic et al, 2018;Ray et al, 2019a), facilitator quality and course reliability have positive relationships with intention to take up courses from an e-Learning platform. Some possible reasons can be: First, earlier researchers have found that course quality (Li et al, 2011;Yang et al, 2017) and course flexibility (Liao et al, 2011) has a positive influence on usage-intention.…”
Section: Resultsmentioning
confidence: 60%
“…Because skill is often measured as an outcome rather than as a determinant, limited research exists with regard to the predictive association between skill and implementation. One study found a positive association between clinician skill and client outcomes in the implementation of an EBP in family court (Berkel et al., ).…”
Section: Section 1: What Have We Learned From the Disaggregation Paramentioning
confidence: 99%
“…Among the latter, factor loadings were close to the threshold in many of the studies, with some above and below the cut-off and other indicators (e.g., model fit) close to those considered high quality. For example, a study by Berkel et al ( 2018 ) was assessed as low quality with a comparative fit index of 0.90—which still represents quite good model fit. Despite over half of the studies not meeting COSMIN criteria, the measures are mostly capturing their intended constructs providing evidence that assessment results can be trusted.…”
Section: Discussionmentioning
confidence: 99%